Multiwall Carbon Nanotube Coated with Conducting Polyaniline Nanocomposites for Quasi-Solid-State Dye-Sensitized Solar Cells - Mohammad Rezaul Karim; Ashraful Islam; M. D. Akhtaruzzaman; Liyuan Han; Abdurahman Al-Ahmari (Journal of Chemistry)
Multiwalled carbon nanotube (MWNT) coated with conducting polyaniline (PAni) nanocomposites has been enforced as for quasi-solid-state electrolyte layer in the dye-sensitized solar cells (DSSCs), and the incorporation of MWNT-PAni nanoparticles on the cell performance has been examined. The MWNT-PAni nanoparticles exploited as the extended electron transfer materials, which can reduce charge diffusion length and serve simultaneously as catalyst for the electrochemical reduction of I3-. An ionic liquid of 1-methyl-3-propyl-imidazolium iodide (PMII) together with the hybrid MWNT-PAni nanocomposites was placed between the dye-sensitized porous TiO2 and the Pt counter electrode without adding iodine and achieved a moderately higher cell efficiency (3.15%), as compared to that containing bare PMII (0.26%).